The Effects Of Shifting Temperature On The Growth Of Listeria Monocytogenes And Salmonella Typhimurium In Goat Milk Samples Collected From Local Dairy Farms - Migeemanathan, Suguna (2013)
The main objective of this study was to determine the adaptation and survival curves of Listeria monocytogenes and Salmonella Typhimurium in goat milk samples collected in local dairy farm in Penang Island. This research was conducted to understand the effects of shifting L. monocytogenes and S. Typhimurium from 37°C to various selected stress temperature in goat milk samples as growth media. The study was divided into 3 main parts. First part of the study was to determine the prevalence microorganisms and pathogens especially L. monocytogenes, S. Typhimurium, total plate count, yeast and mould count and coliform count in goat milk samples from 2 farms. The second part was to establish the growth profile for these two pathogens at 37°C in Tryone Soy Broth media. From the plotted growth curve, stationary phase at 10-7 CFU/ml at 18 and 10 hours of growth was used as the starting inoculum for the stress conditions for L. monocytogenes and S. Typhimurium, respectively. In the third part of study, these pathogens were grown at 37°C in TSB medium before shifting to goat milk at different temperature ranging from 0°C to 90°C. Results of shifting L. monocytogenes and S. Typhimurium from 37°C to lower temperatures from 0 up to 15°C showed bacteriostatic effects, while shifting from 37°C to 25°C showed the ability of L. monocytogenes and S. Typhimurium to grow gradually in goat milk. In contrast, shifting of L. monocytogenes and S. Typhimurium to higher temperatures (from 50°C to 70°C) exhibited growth of both pathogens after few hours of stress and demonstrated straight-line death kinetics.